2005
DOI: 10.1590/s1677-55382005000100010
|View full text |Cite
|
Sign up to set email alerts
|

Laparocopic ureteral reimplantation in ureteral stenosis after gynecologic laparoscopic surgery

Abstract: Pelvic surgery is the most common cause of iatrogenic ureteral injury, and traditionally repair of such injuries requires laparotomy. We report the case of a 48-year-old woman with an iatrogenic ureteral injury after laparoscopic ophorectomy which was laparoscopically reimplanted using the Lich-Gregoire technique. Total operating time was 150 minutes and estimated blood loss was 100 mL. Two months after surgery she is asymptomatic with normal renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
4
0
Order By: Relevance
“…The Da Vinci system clearly enables physicians to safely and effectively perform even the most complex reconstructions of the UT, relying on a 10‐ to 12‐fold magnification, without losing 3D vision and with an extremely high instrument maneuverability that exceeds that of the human wrist (4). However, it could be argued that the UT may be successfully reconstructed even with standard endoscopic devices (14–17), but the experience gained thus far is concentrated within a highly specialized unit and is still very much in its infancy. The approach we used was best suited to our environment and experience at the time of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The Da Vinci system clearly enables physicians to safely and effectively perform even the most complex reconstructions of the UT, relying on a 10‐ to 12‐fold magnification, without losing 3D vision and with an extremely high instrument maneuverability that exceeds that of the human wrist (4). However, it could be argued that the UT may be successfully reconstructed even with standard endoscopic devices (14–17), but the experience gained thus far is concentrated within a highly specialized unit and is still very much in its infancy. The approach we used was best suited to our environment and experience at the time of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Branco et al [3] concluded that in lower ureteral strictures and in cases of a long stricture that will make the length of the ureter insufficient for anastomosis, reimplantation should be the preferred technique [3].…”
Section: Commentmentioning
confidence: 99%
“…The urinary tract is one of the most common extragenital organs that are influenced by endometriosis. During endometriosis surgery, the rate of ureter involvement varies between 0.08% and 1% [2][3][4]. The incidence increases to 4.4% when deep endometriosis is involved and up to 11.2% when nodules larger than 3 cm are found [5].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of iatrogenic ureteral injury is reported to be 0.14%, and the average time between the procedure and recognition of injuries is 3.1 days [3]. The ureteral injury cases reported in the literature mainly occurred during the perioperative period [4]. In some cases, four months elapsed between surgery and the presentation of ureteral stricture injury [5].…”
Section: Introductionmentioning
confidence: 99%